ICT: What does it all mean? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
ICT: What does it all mean?, Developments, issue 16, DFID, 2001 New developments can make a huge difference to our lives. Telephones, radios, email, videos, faxes: so many of us take these communication technologies for granted. But for mill